PENGARUH PENGGUNAAN MEDIA INTERAKTIF DISERTAI PENGISIAN TTS TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI DI SMAN 2 LENGAYANG KABUPATEN PESISIR SELATAN - Pramanda Elva, Widia; nerita, siska; Susanti, Diana (Pendidikan Biologi, 2014)
ABSTRACT   In  the  learning  process  the  teacher  as  the  facilitator  should  be  able  to  use  the  varyingstrategies and media, so that stud ents learn more in the spirit and learning process more interesting,so that student learning outcomes for the better, because of the low student learning outcomes arecaused  b y many factors, both factors of students and factor of the teacher. Therefore, teachers canuse  a  variety  of  strategies  and  media  are  varied,  so  that  the  goal  can  be  achieved  with  goodlearning.  One  of  them  is  the  use  o f  interactive  media  with  charging  TTS,  This  study  aims  todetermine  the  effect  of  the  use  of interactive med ia with  charging TTS  on learning outcomes inbiology  class  XI  student of SMAN  2  Lengayang, This  research  is  an  experimental  study  with  adesign  Rando mized  Control  Group  Posttest  Only Design. The  population  in  this  study  were  allstudents  of  class  XI  in  SMAN  2  Lengayang  enrolled  in  the  second   semester  of  academic  year200 13 /2014.  Sampling  was  done  by  p urposive  sampling  technique.  Then  by  using  purposivesampling obtained experimental class ( XIIA1 ) and control classes ( XIIA2  ). Data were analyzedusing t-test. Fro m the results of the study revealed that the experimental class had an average value( 74,91 ) is higher than the average value of the control class ( 59,8 ).  After the data were analyzedby t test, obtained the price thi t ung  7, 16 and tt ab e l  1, 67. Thus t c oun t  > t t a bl e ,  which means that H1  isaccepted. In other words, it can be concluded that the use of interactive media  with charging TTShas  an  influence  on  learning  outcomes  in  biology  class  XI  student  of  SMAN  2  Lengayang.